Replicability and reproducibility of research results for human language technology: introducing an LRE special section. - Branco, António; Cohen, Kevin; Vossen, Piek; Ide, Nancy; Calzolari, Nicoletta (Language Resources & Evaluation, 2017)
An introduction is presented in which the editor discusses the articles within the issue on topics including human language technology and replication and reproduction of language research papers.